Sacrectomy with ilio-lumbar stabilization due to low-grade chondrosarcoma of sacrum and iliac wing. Case report of the first surgery performed in the Republic of North Macedonia. - Hasani, I; Popovska, D; Todorova, T; Rushiti, Q; Gramatnikovski, N; Hasani Jusufi, A (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences, 2021)
Low - grade chondrosarcomas are primary malignant bone tumors that are resistant to chemo- and radiotherapy and are treated surgically. Sacral localization makes surgical resection technically difficult due to position, anatomic structures involved, and large tumor size at detection. The risk of complications is high. We present the introduction of a novel surgical technique in our country, sacrectomy with ilio-lumbar stabilization. This was performed on a 67-year-old man with low-grade chondrosarcoma of the sacrum with sacroiliac joint involvement. The procedure was performed via an antero-posterior approach in two stages. Ilio-lumbar fixation with a mesh cage bridge was used to obtain spinopelvic continuity and stability. Sacrectomy is a technically demanding procedure that requires careful preoperative planning and a multidisciplinary approach, as well as high level of surgical experience.
Keywords: chondrosarcoma; sacrectomy; ilio-lumbar stabilization